A stress concentration-free bonded arcan tensile compression shear test specimen for the evaluation of adhesive mechanical response. (September 2015) - Créac'hcadec, R.; Sohier, L.; Cellard, C.; Gineste, B.
Abstract: Adhesively bonded structures are increasingly used in the industry: aerospace, aeronautics, automotive and nautical fields. It is thus necessary to characterize the behavior of an adhesive in an assembly from an experimental point of view to a modeling one. The development of reliable models needs very good tests to define the performances of the adhesive used. The modified Arcan test developed by Cognard et al. is an interesting test. However it is difficult to use. The work presented in this paper deals with an evolution of this test called the Arcan Tensile/Compression–Shear Test (Arcan TCS). It simplifies the previous approach taking also into account the influence of the edge effects with the development of a new geometry of the beaks close to the adhesive. It is suited to apply tensile/compression–shear loadings to the adhesive. The test specimen proposed was designed and manufactured to improve the modified Arcan test without reducing the efficiency of the results also including an improvement of the bonding procedure. This new specimen is validated with finite element simulations and tested with an epoxy adhesive to determine the load–displacement behavior and the envelopes at failure.